2010
DOI: 10.1093/ejechocard/jeq067
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interventricular and right-intraventricular dyssynchrony in patients with surgically repaired tetralogy of Fallot by two-dimensional speckle tracking

Abstract: Interventricular and right-intraventricular dyssynchrony are detectable in patients after TOF repair by 2D speckle tracking. Reduced RV myocardial deformation and QRS prolongation are the main factors associated with the observed dyssynchrony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…1,2 Similarly, right bundle branch block (RBBB) is common, and prolonged QRS duration conveys risk for adverse outcome. 3 Although electromechanical abnormalities are recognized in this population, 2,[4][5][6] specific patterns of regional mechanical abnormalities induced by abnormal electric activation associated with RBBB have not been studied. In left bundle branch block (LBBB), abnormal electric activation leads to a typical mechanical dyssynchrony pattern characterized by early septal activation, observed echocardiographically as a septal flash, with concomitant lateral wall prestretch and late contraction of the early-stretched lateral wall.…”
mentioning
confidence: 99%
“…1,2 Similarly, right bundle branch block (RBBB) is common, and prolonged QRS duration conveys risk for adverse outcome. 3 Although electromechanical abnormalities are recognized in this population, 2,[4][5][6] specific patterns of regional mechanical abnormalities induced by abnormal electric activation associated with RBBB have not been studied. In left bundle branch block (LBBB), abnormal electric activation leads to a typical mechanical dyssynchrony pattern characterized by early septal activation, observed echocardiographically as a septal flash, with concomitant lateral wall prestretch and late contraction of the early-stretched lateral wall.…”
mentioning
confidence: 99%
“…Patients with dysfunctional RVOT conduits have been shown to exhibit dyssynchronous interventricular contraction associated with factors such as baseline RV strain, EF, and end-systolic and diastolic volumes. 35 In a cohort of patients with TOF, LV dyssynchrony has been associated with ventricular tachycardia and death.14 Given these associations, we chose to investigate the impact of TPV replacement on ventricular synchrony. Several measures were investigated given the lack of general consensus in the literature regarding the most appropriate index of ventricular synchrony; as well, we included a new measure known as cross-correlation delay which is potentially more robust than traditional indices.…”
mentioning
confidence: 99%
“…Patients with dysfunctional RVOT conduits have been shown to exhibit dyssynchronous interventricular contraction associated with factors such as baseline RV strain, EF, and end-systolic and diastolic volumes. 35 In a cohort of patients with TOF, LV dyssynchrony has been associated with ventricular tachycardia and death.…”
mentioning
confidence: 99%
“…We utilized strain and SR imaging so as to overcome this limitation by measuring the actual extent of stretching or contraction. Mueller et al (31) suggested that 2-D speckle tracking could provide information on the RV function but it required further investigation. More recently, in children, three-dimensional (3D) echocardiography has been found to have an excellent correlation with CMR in the assessment of the RV volumes and function.…”
Section: Discussionmentioning
confidence: 99%